Baroja and the "Genesis": towards a hypertextual reading of "El Árbol de la Ciencia" - Hernández Lobato, Jesús (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
This paper aims to provide a new overall reading of El árbol de la ciencia by means of a detailed analysis of its rich hypertextual dialogue with the book of Genesis and European literature as a whole. All through his novel Baroja manages to spread a set of clues or intertextual indications that let the attentive reader reconstruct the allegorical meaning of his work, beyond its merely autobiographical, philosophical or sociohistorical aspects, which have been largely the main topic of so many papers and studies before. This new look at the polyphonic interplay between interwoven literary discourses (regarding western exegetical tradition, Jewish esotericism or medieval commonplaces) and the biblical text of Genesis provides us a more extensive and nuanced point of view about the meaning(s) of the novel, always open to the most surprising games of allusive reutterance and critical review of inherited material.